2021
DOI: 10.1111/1462-2920.15649
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic potential and survival strategies of microbial communities across extreme temperature gradients on Deception Island volcano, Antarctica

Abstract: Active volcanoes in Antarctica have remarkable temperature and geochemical gradients that could select for a wide variety of microbial adaptive mechanisms and metabolic pathways. Deception Island is a stratovolcano flooded by the sea, resulting in contrasting ecosystems such as permanent glaciers and active fumaroles, which creates steep gradients that have been shown to affect microbial diversity. In this study, we used shotgun metagenomics and metagenome-assembled genomes to explore the metabolic potentials … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 117 publications
0
6
0
Order By: Relevance
“…Network analyses concluded that the overall complexity of interactions among bacteria is higher in geothermal environments than in lava caves. Bendia et al ( 2021 ) reported a similar pattern of greater complexity in microbial communities along a thermal gradient. This observation may reflect the more extreme nature of the environment and lower diversity overall, a situation in which more synergistic metabolic interactions may be required for survival, with fewer individual strains or species able to fulfill the required ecological roles (greater number of hubs).…”
Section: Discussionmentioning
confidence: 78%
“…Network analyses concluded that the overall complexity of interactions among bacteria is higher in geothermal environments than in lava caves. Bendia et al ( 2021 ) reported a similar pattern of greater complexity in microbial communities along a thermal gradient. This observation may reflect the more extreme nature of the environment and lower diversity overall, a situation in which more synergistic metabolic interactions may be required for survival, with fewer individual strains or species able to fulfill the required ecological roles (greater number of hubs).…”
Section: Discussionmentioning
confidence: 78%
“…The DNA used to perform the metagenomic sequencing was extracted from samples collected in the same area where the samples for isolating bacteria were obtained. The DNA extraction and metagenome sequencing (Shotgun) methods were described by Bendia et al (2021) . Reads were filtered using SICKLE software ( Joshi and Fass, 2011 ), using a minimum Phred score of 30.…”
Section: Methodsmentioning
confidence: 99%
“…Metagenomic approaches, in which the total DNA is extracted directly from environmental samples and shotgun-sequenced ( Kunin et al, 2008 ), have been used to investigate microbial communities and their functions in various extreme environments, such as thermal pools ( Wilkins et al, 2019 ), desert biological soil crusts ( Meier et al, 2021 ), permafrost ( Woodcroft et al, 2018 ), and Antarctic microbial mat and soil ( Zaikova et al, 2019 ; Bendia et al, 2021 ). Nearly complete genomes have been assembled from shotgun-sequenced metagenomes from these environments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic studies suggested that the other reverse gyrase TopR2 in Sulfolobales may have another more important function [ 122 ]. Based on previous work, the requirement of reverse gyrase activity for hyperthermophiles [ 28 , 123 ] may be related to DNA protection and repair in addition to positive DNA supercoiling [ 29 , 124 , 125 ].…”
Section: Physiological Functions Of Type Ia Topoisomerasesmentioning
confidence: 99%